Pengaruh Terapi Renang Pada Perkembangan Motorik Kasar dan Imunitas Bayi 0-12 Bulan Pada Pandemi COVID-19 - awwalul wiladatil qodliyah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: This study aims to determine the effect of swimming therapy on gross motor development and immunity of infants 0-12 months.Methods: The design of this research is Pre and Post-Test with One Group Design. One group was given swimming therapy treatment, carried out three times a week for four weeks, for 10 minutes. Before being given treatment, the baby was first tested using the Denver Development Screening Test (DDST) to assess the baby's gross motor development and assess the baby's immunity; then, a post-test was carried out four weeks later. This research was conducted in September 2021 and took place at TPMB Sri Wahyuni. The population in this study were all infants aged 0-12 months who attended swimming therapy, totalling 25 people.Results: Based on the research, it is known that the sex of most babies is 1re girls (64.00%). Most babies aged 5-8 months were 17 people (68.00%), and included in the category of good nutrition were 15 people (60.00%). This study showed a decrease in the pre-test of 16 babies in the caution category, decreased by two people (10%) to only 14 babies. In the normal category, the data increased by two babies (10%), which can be seen from the pre-test; seven babies were included in the normal category to 9 babies. This study’s results indicate a decrease in the results; initially, at the time of the pretest, 13 babies who were included in the low immunity category experienced a decrease of 3 people (12%) to only ten babies. There was an increase in data by three babies (12%), which can be seen from the pre-test results of 12 babies included in the good category to 15 babies. The results showed a significance value of 0.000 with an alpha of 5%.Conclusion: Swimming therapy affects gross motor development and immunity of infants aged 0-12 months TPMB Sri Wahyuni. The baby's mother needs to pay attention to the baby's needs, including meeting the baby's stimulation needs to support the baby's development, for example, by swimming and other sports.